Predicting The Evolution and Effects of The Asia Crisis from The OECD Perspective - Richardson, Pete (OECD Economics Department Working Papers, 2000)
Over the past two years, the key trading economies in SE Asia experienced major economic crises, involving financial turbulence, large capital outflows and currency depreciations. These, in turn, resulted in severe financial constraints and business failures and required major domestic adjustments and massive swings in their currentaccount balance of payments positions. The associated economic recessions had major effects on the economies in question and, because of constraints on their capacity to invest and import, a significant impact on the rest of the world, so that world trade and output growth slowed significantly and world commodity markets weakened substantially over the period. This paper looks at the wider macroeconomic consequences of the Asia crisis and their predictability from the perspective of the OECD countries. In doing so it examines some of the major aspects of the Asia crisis, its effects on the world situation and their predictability, assisted by the OECD's ...